Relación entre regulación emocional, alexitimia y síntomas depresivos en estudiantes del programa de Beca 18 de una universidad privada de Arequipa - Lewis Paredes, Jessica (2022)
This research analyzes the relationship between emotional regula tion strategies, alexithymia and depressive symptoms in students of Beca 18 College Scholarship of a private university of Arequipa city. A descriptive-explanatory study was designed to be applied for 114 students of both sex, which ages were between 17 and 22 years old. The questionnaire technique was used to measure the variables. Three measures were used: The Emotional Regulation Questionnaire Peruvian version (ERQP), the Spanish adaptation from Toronto Alexithymia Scale (TAS-20) and Zung Scale for Depression. The results showed that alexithymia, suppression strategy (r = 0.395; p < 0.001) and depres sion (r = 0.319; p = 0.001) were related significantly. The final conclusion is that alexithymia and the use of suppression lead to depressive symptoms in the students. Considering these results, we recommend implementation of psychologic strategies for emotional regulation and other healthy issues to prevent depression in students.